Peningkatan Hasil Belajar Matematika Materi bangun Datar Melalui Penerapan Model Pembelajaran Kontekstual dengan Media PANGRAM - Dewi Aulia Putri; Pratiwi, Ika Ari; Sofiyati, Dewi; Setiyana, Aris (Kompetensi : Jurnal Pendidikan dan Humaniora Fakultas Keguruan dan Ilmu Pendidikan UNIBA, 2025)
This investigation aims to evaluate the effectiveness of the contextual approach integrated with PANGRAM (a combination of plane geometry board and tangram) in enhancing mathematics learning outcomes. The study involved twelve fourth-grade students at SD 3 Barongan. Thes study was conducted form February to March 2025. Employing a classroom action research methodology conducted through two cycles, each comprising planning, implementation, observation, and reflection phases. Data collection techniques included learning outcome evaluation tests and documentation throughout the study.  Student achievement was measured through post-action assessment. Success indicators were established at a minimum 80% classical mastery achievement. The analytical framework combined descriptive qualitative and quantitative approaches. Results demonstrated a marked improvement in student mastery percentages, progressing from 42% in the pre-cycle phase to 67% in the first cycle, ultimately reaching 92% in the second cycle. Based on these findings  can be concluded that the implementation of a PANGRAM-based contextual approach effectively enhances fourth-grade students' comprehension and learning outcomes in plane geometry topics.